Control of Organic Impurities in Semisynthetic Antibiotics - E. L. Kovaleva; K. S. Arhipova; E. A. Bulova; A. A. Stralkovskaya; O. O. Terentieva (Регуляторные исследования и экспертиза лекарственных средств)
In 2012, the European Medicines Agency (EMA) adopted a guideline, which divided all antibiotics into groups according to the manufacturing process and established acceptance criteria for organic impurities for each of the groups.The aim of the study was to justify the requirements and methodological approaches to setting the limits for organic impurities in semisynthetic antibiotics.Materials and methods: the authors analysed the requirements established by the leading world pharmacopoeias and the State Pharmacopoeia of the Russian Federation regarding the control of organic impurities in semisynthetic antibiotics, using the example of four semisynthetic antibiotics: doxycyline hyclate, clarithromycin, meropenem, and ceftriaxone. The study used the methods of comparative analysis and content analysis. Results: the study demonstrated that the organic impurity profiles of the analysed active substances and the corresponding finished medicinal products often differ significantly across the leading pharmacopoeias, either qualitatively or quantitatively. The Russian, European, and United States pharmacopoeias provide for the use of impurity reference standards in the test procedures for the determination of impurities in active substances of the semisynthetic antibiotics in question, whereas the Japanese Pharmacopoeia allows the use of non-compendial reference substances in the assessment of the chromatographic system separation power.Conclusions: the ability of a pharmacopoeial text to cover a variety of medicinal products coming to the Russian market from different countries has become a vital issue. This includes covering the impurity determination procedures, reference standards, and limits used, because general-purpose methods and limits do not always allow for correct assessment of impurity profiles in substances produced by different manufacturing processes. The current USP practice is to include various impurity control procedures in monographs on medicinal products, and the limits may also vary. This approach may be applied in the State Pharmacopoeia of the Russian Federation as well.